2016
DOI: 10.1017/s0007114516003676
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in metabolite content in the liver of magnesium-deficient rats

Abstract: Mg deficiency induces various metabolic disturbances including glucose metabolism in the liver. However, no comprehensive information is currently available on the metabolic pathways affected by Mg deficiency. The present study examined metabolite content in the liver of Mg-deficient rats using a metabolomic analysis. In this study, 4-week-old, male Sprague-Dawley rats were fed a control diet or a Mg-deficient diet for 8 weeks. The metabolomic analysis identified 105 metabolites in the liver, and significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Given this, NIPAL1 could play a role in facilitating magnesium entry into the Golgi in a manner that directly impacts the ionic flux governing the trafficking of insulin vesicles within the organelle. A potential driving force may be magnesium's role as a primary ATP-binding co-factor (Mg-ATP) involved in facilitating phosphate transfer reactions (5,6) that are critical for fueling secretory granule movements (45,46) and both glycolysis and the citric acid cycle (47,48). Both Golgi and mitochondrial functions are highly dependent on the availability of ATP delivered by bound magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, NIPAL1 could play a role in facilitating magnesium entry into the Golgi in a manner that directly impacts the ionic flux governing the trafficking of insulin vesicles within the organelle. A potential driving force may be magnesium's role as a primary ATP-binding co-factor (Mg-ATP) involved in facilitating phosphate transfer reactions (5,6) that are critical for fueling secretory granule movements (45,46) and both glycolysis and the citric acid cycle (47,48). Both Golgi and mitochondrial functions are highly dependent on the availability of ATP delivered by bound magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that 0.1 µmol/L RSG treatment induced increased Ca and K levels in the cells that may show inducing the insulin secretion ( Figure 2 ). On the other hand, Mg is essential for glycolysis, citric acid cycle, increasing insulin sensitivity and improving lipid profile [34] [35] [36] [37] [38] . We showed that 0.1 µmol/L RSG treatment caused an increase in magnesium concentrations that may be explained by the necessity of Mg in the cells to improve insulin sensitivity and the lipid profile ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then the solution was treated as described previously (Shigematsu et al . ). Briefly, the samples were lyophilized, and then 40 μL of 20 mg/mL methoxyamine hydrochloride (Sigma‐Aldrich) was added, dissolved in pyridine for oximation.…”
Section: Methodsmentioning
confidence: 97%
“…A sample of 50 lL of serum was mixed with 5 lL of 1 mg/mL 2-isopropylmalic acid (Sigma-Aldrich, Tokyo, Japan) in distilled water as an internal standard, and 250 lL of methanol/chloroform/water (2.5/1/1). Then the solution was treated as described previously (Shigematsu et al 2016). Briefly, the samples were lyophilized, and then 40 lL of 20 mg/mL methoxyamine hydrochloride (Sigma-Aldrich) was added, dissolved in pyridine for oximation.…”
Section: Non-targeted Analysis Of Low Molecular Weight Metabolites Inmentioning
confidence: 99%